2023
DOI: 10.1590/1678-4162-12774
|View full text |Cite
|
Sign up to set email alerts
|

Blood concentrations of calcium, phosphorus and magnesium and dietary cation-anion difference in dairy cows

Abstract: The objective of this study was to identify the effect of pre and postpartum DCAD on serum levels of calcium, phosphorus, and magnesium in peripartum Holstein cows. Blood samples were collected from 56 cows (18 primiparous and 38 multiparous) on days -7, +7, +14 and +28 relative to parturition, to determine serum levels of total and ionized calcium, phosphorus, magnesium, and albumin; diet samples for determination of calcium, phosphorus, magnesium and DCAD were collected at the same moments and urine samples … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
1
0
0
Order By: Relevance
“…Magnesium is absorbed in the rumen, and its metabolism is connected to other trace minerals. In this study, calcium and magnesium exhibited similar variations, with minimum values observed at one week postpartum and maximum values found at one month postpartum (Silva et al., 2023). In addition, a positive and statistically significant correlation between magnesium and calcium concentration was identified at four weeks postpartum in primiparous cows; animals with high concentrations of magnesium and calcium showed a reduced calving interval.…”
Section: Discussionsupporting
confidence: 75%
“…Magnesium is absorbed in the rumen, and its metabolism is connected to other trace minerals. In this study, calcium and magnesium exhibited similar variations, with minimum values observed at one week postpartum and maximum values found at one month postpartum (Silva et al., 2023). In addition, a positive and statistically significant correlation between magnesium and calcium concentration was identified at four weeks postpartum in primiparous cows; animals with high concentrations of magnesium and calcium showed a reduced calving interval.…”
Section: Discussionsupporting
confidence: 75%